Study on Serum Electrolytes in Sickle Cell Disease Patients on Hydroxyurea Therapy Non-hydroxyurea Therapy - Madhuri, M; Rajkumari, D.M.M (Indian journal of clinical biochemistry, 2022)
Sickle disease affects millions of people worldwide. Where as in India, prevalence is high in Orissa, Madhya Pradesh, Maharashtra, western regions of Gujarat and Chhattisgarh. The morbidity and mortality associated with the disease, complications and sickle cell crisis is a significant health issue. Hydroxyurea is an anticancer agent, which proved to be the wonder drug in lower doses in sickle cell disease. The main aim of the study is to evaluate the serum electrolytes level in sickle disease patients and find out the effect of hydroxyurea. Sickle cell disease patients and 20 normal individuals as controls are included in the study. 11 patients on hydroxyurea therapy and 13 are non-hydroxyurea therapy. The serum levels of sodium, potassium, chloride, calcium, magnesium and phosphate were estimated in all the study subjects. There is significant difference observed among Total Bilirubin, Urea, and Creatinine and chloride levels among Sickle disease patients compared with normal individuals. No much significant results were observed among patients on hydroxyurea therapy and non-hydroxy urea therapy except for Total bilirubin and Sodium levels. Electrolytes plays crucial role in the pathophysiology of sickle cell disease, but hydroxyurea therapy does not seem to alter the electrolyte levels in patients.